2022
DOI: 10.3389/fbioe.2022.910578
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic Traps for Efficient Bead and Cell Trapping and Formation of Aggregates of Controlled Size and Composition

Abstract: We present a microfluidic dielectrophoretic-actuated system designed to trap chosen single-cell and form controlled cell aggregates. A novel method is proposed to characterize the efficiency of the dielectrophoretic trapping, considering the flow speed but also the heat generated by the traps as limiting criteria in cell-safe manipulation. Two original designs with different manufacturing processes are experimentally compared. The most efficient design is selected and the cell membrane integrity is monitored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The photoresist residues remaining in the buried channels were then cleaned using oxygen plasma (GIGAbatch, PVA TePla). The top PDMS channels were then molded, aligned and permanently bonded to the electrodes and glass channels as described by Lipp et al 19 The full fabrication process is shown in Fig. S1, † and pictures of the fabricated combined traps and the whole final chip in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photoresist residues remaining in the buried channels were then cleaned using oxygen plasma (GIGAbatch, PVA TePla). The top PDMS channels were then molded, aligned and permanently bonded to the electrodes and glass channels as described by Lipp et al 19 The full fabrication process is shown in Fig. S1, † and pictures of the fabricated combined traps and the whole final chip in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The effects are thus orthogonal for an independent manipulation of the two micro-sized particles. The method relies on the combination of two trapping methods based on planar hydrodynamic trapping of cells 18 and dielectrophoretic (DEP) trapping, 19 both physical principles being widely used to precisely manipulate and trap single cells. 20,21 The fabrication processes were successfully implemented sequentially to provide a novel device with both capabilities.…”
mentioning
confidence: 99%
“…The remaining photoresist residues remaining in the buried channels are then cleaned using an oxygen plasma (GIGAbatch, PVA TePla). The top PDMS channels are then molded, aligned and permanently bonded to the electrodes and glass channels as described in (19). The full fabrication process is illustrated in Figure S4 in supplementary material, and pictures of the fabricated combined traps and the whole final chip respectively in Figures S5 and S2A.…”
Section: Methodsmentioning
confidence: 99%
“…This latter is composed of an upstream DEP actuated deviation system capable of steering the incoming particles to specific streamlines (22), followed by an expansion of the channel and two lines of DEP traps. Each line is made of coplanar electrodes and comprises four distinct trapping units capable of focusing the particles to one point in three dimensions (19) as well as a bypass zone to which unwanted particles can be deviated to leave the chamber. The upstream line is named the synchronization line because its role is to synchronize the arrival of particles to the second line once the amount of particles per trap is reached.…”
Section: Principle Of Operation: Combining Hydrodynamicmentioning
confidence: 99%
See 1 more Smart Citation